2009
DOI: 10.4142/jvs.2009.10.4.337
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the clinical signs of chronic endometritis with ovarian cysts and body condition loss in German Holstein Friesian cows

Abstract: The objective of this retrospective field study was to associate the type and smell of discharge, the size of the uterus, the ovarian and treatment status, and the time to diagnosis of animals with chronic clinical endometritis (CCE) with the incidence of ovarian cysts and with a marked loss in body condition in German Holstein Friesian cows. Two hundred and sixty-four cows diagnosed with CCE from day 14 to day 42 postpartum participated in this study. In addition, 100 days milk production and the parity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Additionally, healthy cows had a lower incidence of cystic follicles (Maquivar et al, 2015). Tsousis et al (2009) also had found a greater incidence of ovarian cysts in cows with clinical endometritis diagnosed from 14 to 42 DIM.…”
Section: Effects Of Uterine Disease On Ovarian Structures and Their Pmentioning
confidence: 89%
“…Additionally, healthy cows had a lower incidence of cystic follicles (Maquivar et al, 2015). Tsousis et al (2009) also had found a greater incidence of ovarian cysts in cows with clinical endometritis diagnosed from 14 to 42 DIM.…”
Section: Effects Of Uterine Disease On Ovarian Structures and Their Pmentioning
confidence: 89%
“…Cows aged between 2-4 years have a small pelvis compared to older cows and thus greater degree of uterine damage leads to uterine infection (Potter et al, 2010). Tsousis et al, (2009) found out that cows in their first parity had persistent purulent discharge compared to older cows which could have been as a result of calving assistance leading to uterine lesions. Endometritis was more prevalent in mature cows where cows in their third or higher lactation had a prevalence of 21% compared to 13% for cows in first and second lactation (LeBlanc et al, 2002).…”
Section: Age Of Dammentioning
confidence: 99%
“…Lowest incidence of postpartum metritis occurred in cows between 2 and 4 years of age and was highest in cows older than 7 years (Smith and Risco, 2002). Young cows are prone to uterine injuries during assisted calving and thus predisposing them to uterine infections (Konyves et al, 2009;Tsousis et al, 2009). Cows aged between 2-4 years have a small pelvis compared to older cows and thus greater degree of uterine damage leads to uterine infection (Potter et al, 2010).…”
Section: Age Of Dammentioning
confidence: 99%
See 1 more Smart Citation
“…Endometritis induces ovarian disorder, resulting in subfertility in dairy cattle (Herath et al, 2006(Herath et al, , 2007Williams et al, 2007). A relationship between endometritis and COD has been reported in dairy cattle (Kesler and Garverick, 1982;Bosu and Peter, 1987;Tsousis et al, 2009). The relationships among uterine infection, endotoxin production, and resumption of postpartum ovarian activity have been established (Mateus et al, 2003).…”
Section: Introductionmentioning
confidence: 99%